(untitled) (Al-Academy, 2016)
Addressed the problem of the research is marked (experimentation in caves fee) concept and its role in experimentation deviate Display Num formal charges caves. The search came in four sections: general framework for research and identified the research problem and the need for him. With an indication of the importance of his presence. Then specify the search for the goals of (revealed the nature and role of experimentation in determining the nature of Manifesting fee documented on the walls of caves), followed by the establishment of the three search limits (objectivity, the temporal and spatial) were then determine the terms related to the title. Then provide the theoretical framework and indicators that resulted from academic theorizing of the subject. The researcher has identified three addresses implied within this framework to ensure reading placed search according to the various frameworks tariff. Were as follows: the concept of experimentation. Experimentation in caves charges. Media pressure on the experimenting with painters caves. The third chapter was devoted to the search procedures, through thoughtful community detection and sample selected from (6 works) and then specify the search tool and determine the methodology, followed by an analysis of the sample. The fourth chapter included the search results, including:1.grooves technique is subject to a workout, to makes the close forms of sensory origin, but only signals the like.2.Painter sought in the selection of a flat area of the wall of the cave, showing his desire to make Treatment copyrighted material for aesthetic value, but that this has led to specific forms without the other.3.Coloring lines, gives the painter freedom and control over technique grooves, so tool play an important role in the path of experimentation and results.4.Shows interest painter to the outer limits, or peripheral lines, because they provide a direct definition of the form, due to the role of reference agreed upon between him and the viewer, especially contemporary to him